SFM Fetal Therapy Practice Guidelines: Fetal Interstitial Laser - Sharma, K. Aparna; KV, Seneesh; Chawla, Latika; Rana, Anubhuti (Journal of Fetal Medicine, 2023)
Fetal laser therapy was first used in complicated monochorionic pregnancies such as twin-to-twin transfusion syndrome or twin-reversed arterial perfusion sequence. There are some other less common indications such as amniotic band syndrome, chorioangiomas, lower urinary tract obstructions, sacrococcygeal teratomas, and fetal thoracic masses. These practice guidelines discuss the indications, contraindications, and risks of the procedure along with information for patients and draft consent form.
Keywords: chorioangioma; fetal therapy; interstitial laser; selective fetal reduction